Representasi Budaya Membaca pada Novel Anak Be a Perfect Person in Just Three Days! Karya Stephen Manes (Kajian Semiotik) - Dewi, Sarwendah Puspita (Titian: Jurnal Ilmu Humaniora, 2024)
This research aims to explore the representation of reading culture in the novel Be a Perfect Person in Just Three Days! the work of Stephen Manes using Charles Sanders Peirce's semiotic approach. The method used in this research is a qualitative method with Charles Sanders Peirce's semiotic approach (the concept of the trichotomy of signs, namely Icon, Index and Symbol). Reading scenes, especially those carried out by Milo, are depicted in almost all chapters in the book. Repetition of reading activities carried out by the main character in the book Be a Perfect Person in Just Three Days! generally represents reading culture. The reading culture in this children's novel is represented through signs that represent icons, indexes and symbols. Abstrak Penelitian ini bertujuan untuk mengeksplorasi representasi budaya membaca dalam karya novel Be a Perfect Person in Just Three Days! karya Stephen Manes dengan menggunakan pendekatan semiotik Charles Sanders Peirce. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan semiotik Charles Sanders Peirce (konsep trikotomi tanda, yakni Icon, Index dan Symbol). Adegan membaca, khususnya yang dilakukan oleh Milo, nyaris tergambar di semua bab dalam buku. Repetisi kegiatan membaca yang dilakukan oleh tokoh utama dalam buku Be a Perfect Person in Just Three Days! ini secara garis besar sudah merepresentasikan budaya membaca. Budaya membaca dalam novel anak tersebut direpresentasikan melalui tanda yang melambangkan ikon, indeks, dan simbol.